Bicanalicular Canaliculops and its Dacryoendoscopic Findings. Issue 2 (March 2018) - Ramyil, Alice Venyir; Gupta, Shweta; Ali, Mohammad Javed; Naik, Milind N.
Abstract : Canaliculops is a noninflammatory ectasia of the canaliculus and so far only 7 histopathologically confirmed cases have been reported worldwide. The authors present a middle aged female with right-sided bicanalicular cystic swellings associated with punctal agenesis. Ultrasound biomicroscopy showed a cystic dilatation of the canaliculus and dacryoendoscopy showed a cavity lined by whitish canalicular mucosa, thrown into numerous irregular folds with a blind medial end. Histopathological examination confirmed the diagnosis of canaliculops. To the best of authors' knowledge, this is the first description of a bicanalicular canaliculops and its dacryoendoscopic findings. Abstract : This report discusses bicanalicular involvement by canaliculops and its dacryoendoscopic features.